Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Kartu Xl Prabayar pada Mahasiswa Universitas Muhammadiyah Palembang - Rafli, M.; Fitantina; Sudarta (PT Maju Malaqbi Makkarana, 2025)
Satisfaction of XL Prepaid Cards among students at the University of Muhammadiyah Palembang (UMP), both simultaneously and partially. The research is associative, using a questionnaire as the data collection technique. The population consists of 100 UMP students who have used XL Prepaid Cards. The data analysis method combines qualitative and quantitative approaches, employing multiple linear regression, F and t tests, and the coefficient of determination. The results show a positive and significant effect of Product Quality and Service Quality on Customer Satisfaction. The regression equation is Y = 0.435 + 0.596 X1 + 0.244 X2. Simultaneously, Fcount (73.663) > Ftable (2.36) with a significance level of 0.000 < 0.1, indicating a significant joint effect. Partially, Product Quality has a significant effect (tcount = 5.269 > ttable = 1.290, sig. 0.000 < 0.1), and so does Service Quality (tcount = 2.160 > ttable = 1.290, sig. 0.000 < 0.1). The Adjusted R Square value is 59.5%, meaning that Product and Service Quality contribute 59.5% to Customer Satisfaction, while 40.5% is influenced by other factors not examined in this study.